Newly synthesized NiCoFeCrW High-Entropy Alloys (HEAs): Multiple impacts of B4C additive on structural, mechanical, and nuclear shielding properties - Gul, Ali Oktay; Kavaz, Esra; Basgoz, Oykum; Guler, Omer; ALMisned, Ghada; Bahceci, Ersin; Tekin, H. O. (Elsevier Sci Ltd, 2022)
High-Entropy Alloys (HEAs) are regarded as potential structural materials for fusion and next-generation fission reactors, which will be required to fulfil growing nuclear energy demands. In this study, a HEA-composite was synthesized by adding B4C to an HEA containing Ni. The microstructure of the obtained HEA-composite was examined and the changes in its mechanical properties were revealed. Additionally, the nuclear radiation shielding properties of the Ni-containing HEA, and the HEA-composite are investigated using experimental and theoretical methods. Our initial findings showed that with the addition of 2.5% B4C to the alloy, the hardness increased more than two times. The addition of B4C to the HEA matrix resulted in a more than 90% and a nearly twofold increase in compressive strength. The shielding qualities of gamma-ray and neutron radiation were investigated using experimental and theoretical approaches. Our findings demonstrated that increasing the B4C reinforcement considerably enhanced the composite material's neutron attenuation capabilities. On the other hand, no significant change in the gamma-ray shielding characteristics of HEA and HEA-composite samples was observed. The gamma-ray shielding characteristics of HEA and HEA-composite samples were compared to those of other alloy shields and commercial products. Our findings indicate that both HEA and HEA-composite samples exhibit superior gamma-ray shielding characteristics when compared to the control samples. It can be concluded that increasing B4C reinforcement may be a multifunctional tool in terms of improving the mechanical properties as well as neutron attenuation properties for advanced applications in nuclear radiation facilities and next-generation fission reactors. Additionally, due to their promising material features and higher gamma-ray shielding capabilities compared to other kinds of alloys and commercial shields, HEAs may be beneficial materials.
Keywords: High-entropy alloys; Composites; Mechanical properties; Neutron; Gamma-ray